Violent geographies fear, terror, and political violence - Gregory, Derek 1951-; Pred, Allan 1936-2007 (Routledge, Taylor & Francis Group, 2007)
Derek Gregory and Allan Pred's Violent Geographies gathers together a group of young and well established geographers to look at how territory and space delimit and shape both terrorism and political violence in wide range of places, from the Middle East to Latin America. In short, the book shows how physical violence, especially terrorism, disrupts the distinction between the global and the local by injecting transnational politics into the intimacies of everyday life. Violent Geographies also shows how terrorism is not simply used by nonstate groups --states use it as well, including many of
Description based upon print version of record